1971
DOI: 10.2320/matertrans1960.12.76
|View full text |Cite
|
Sign up to set email alerts
|

The Main Factors Affecting the Aging of Magnesium-Zinc Alloys

Abstract: Hardness measurements and electron microscopic observations were made to study factors affecting the aging of Mg-Zn alloy and Mg-Zn-(Ag) alloys. In regard to the homogeneous and heterogeneous nucleation in these alloys, direct aging, twostep aging and strain aging were carried out, with the results summarized as follows:the nucleation rate largely depends on the quenching rate, the concentration of zinc and the small amount of silver (0.04wt%).(2) In the C-curves which were obtained by plotting the incubation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…Addition of Cu also increases the eutectic temperature and permits the use of higher solution treatment temperatures. [2,3] The precipitation sequence in the Cu-containing Mg-Zn alloys above 150°C [4] has been reported to be the same as the most probable aging sequence for a binary Mg-Zn alloy: [5][6][7][8][9][10][11][12] SSSS ! solute clusters !…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Addition of Cu also increases the eutectic temperature and permits the use of higher solution treatment temperatures. [2,3] The precipitation sequence in the Cu-containing Mg-Zn alloys above 150°C [4] has been reported to be the same as the most probable aging sequence for a binary Mg-Zn alloy: [5][6][7][8][9][10][11][12] SSSS ! solute clusters !…”
Section: Introductionmentioning
confidence: 98%
“…[14] The precipitation of GP zones was also confirmed by the effect that low-temperature preaging had on hardness and microstructure evolution during subsequent artificial aging. [7,8,15] A more recent study showed that the precipitation in Mg-Zn alloy commences by clustering of Zn atoms, while during aging at intermediate temperatures (up to about 100°C), four to six different types of precipitates were simultaneously present in the microstructure leading to hardening of a significant magnitude. [16] Age hardening at ambient temperature after quenching from the solution heat treatment temperature is common to age-hardenable aluminum alloys; however, this was not observed in age-hardenable magnesium alloys in the past.…”
Section: Introductionmentioning
confidence: 99%
“…For Mg-Zn-Al alloys with compositions lying in the (a-Mg + /) two-phase field and produced by high-pressure die casting or permanent mold casting, recent studies using TEM and convergent-beam electron diffraction patterns [107,108] indicate that primary intermetallic particles in the as-cast condition have a quasi-crystalline structure (point group of m " 3 " 5, quasi-lattice parameter~0.515 nm) and a composition of approximately Mg 55 [109] and Mg 32 (Al,Zn,Cu) 49 [110] intermetallic alloys, but it is smaller than the that (0.528 nm) reported for the icosahedral Mg 38.5 Al 52 Zn 9.5 phase in Al-Mg-Zn alloys. [111] Even though the equilibrium T phase is often regarded as the crystalline approximant of the icosahedral phase, [112] the metastable quasi-crystalline phase does not transform to the T phase after prolonged heating at elevated temperatures such as 598 K (325°C).…”
Section: Phase Equilibria and Precipitationmentioning
confidence: 99%
“…[52][53][54][55][56] The aging curves of two binary Mg-Zn alloys are provided in Figure 5(a). Depending on the alloy composition and aging temperatures, it is commonly accepted in the literature [6,8,30] that the decomposition of the supersaturated solid-solution matrix phase reportedly involves the formation of G.P.…”
Section: Phase Equilibria and Precipitationmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] For example, Mg-5 mass%Zn alloy exhibits age hardening by the precipitation of needle shaped MgZn phase after prolonged aging at $422 K. 10) To date, however, TMT to attain microstructural stability has not been investigated in magnesium alloys.…”
Section: Introductionmentioning
confidence: 99%